Gaucher’s Disease : A Case Report - Prisila, Elvina; Majdawati, Ana (Ahmad Dahlan Medical Journal, 2023)
Gaucher disease is a rare genetic disorder in which a person lacks an enzyme called glucocerebrosidase (GBA). Gaucher disease is an autosomal recessive inherited disorder of metabolism where a type of fat (lipid) called glucocerebroside cannot be adequately degraded. The lack of the GBA causes harmful substances to build up in the lung, liver, spleen, bones, and bone marrow, brain and eyes. These substances prevent cells and organs from working properly. There are three recognized Types of Gaucher disease and each has a wide range of symptoms. Type 1 is the most common, does not affect the nervous system and may appear early in life or adulthood. Many people with Type 1 Gaucher disease have findings that are so mild that they never have any problems from the disorder. Type 2 and 3 do affect the nervous system. A man, 27th, goes to the hospital with pain at upper of left knee, swollen since 3 week ago, hypertension(-), DM (-), history of left knee operation. Traumatic history (-). HB: 14,9mmgr/dl, AL 7,6. AT 186, HMT 43,8%, GDS 95 mg/dl, APTT 34,4. PPT: 11,6, diff eosinophil: 3,2. From the symptoms dan clinical finding from this patient we can make conclusion, the case is typical Gaucher disease type 1.